Allianz and the German insurance business, 1933-1945 - Feldman, Gerald D. (Cambridge University Press, 2001)
This history of the internationally prominent insurance corporation Allianz AG in the Nazi era is based largely on new or previously unavailable archival sources. This book joins a growing body of scholarship based on free access to the records of German corporations in the Nazi era.